2D-RBUC for efficient parallel compression of residuals. (February 2018) - Đurđević, Đorđe M.; Tartalja, Igor I.
Abstract: In this paper, we present a method for lossless compression of residuals with an efficient SIMD parallel decompression. The residuals originate from lossy or near lossless compression of height fields, which are commonly used to represent models of terrains. The algorithm is founded on the existing RBUC method for compression of non-uniform data sources. We have adapted the method to capture 2D spatial locality of height fields, and developed the data decompression algorithm for modern GPU architectures already present even in home computers. In combination with the point-level SIMD-parallel lossless/lossy high field compression method HFPaC, characterized by fast progressive decompression and seamlessly reconstructed surface, the newly proposed method trades off small efficiency degradation for a non negligible compression ratio (measured up to 91%) benefit. Highlights: We propose a SIMD-parallel, lossless, and seamless terrain compression method. We improve the compression ratio of the HFPaC parallel GPU compression method. Desirable features of the HFPaC compression method are mostly preserved. The method benefits from the 2D spatial locality of residuals. The improved method is still highly efficient.